Western and non-western leadership styles and employee wellbeing: a case of a high-power distance context - Ehrnrooth, Mats; Koveshnikov, Alexei; Balabanova, Evgeniya; Wechtler, Heidi (Frontiers in Psychology, 2024)
The study combines an emic and etic perspective to test the relationships between three different (Western and non-Western) leadership styles, that is, transformational, authoritarian, and benevolent paternalistic, and follower emotional exhaustion in a high-power distance context of Russia. It employs hierarchical linear modeling (HLM) to analyse a sample of 403 followers to middle-level managers in Russian organizations. The analysis finds only transformational leadership to be generally negatively associated with emotional exhaustion. However, under conditions of high individual-level power distance orientation among followers, this association diminishes whereas that of authoritarian leadership and exhaustion increases. Benevolent paternalistic leadership is unrelated to emotional exhaustion. The study extends research on the relative importance of Western and non-Western leadership behaviors for employee wellbeing in high-power distance contexts and on how this importance differs across followers, thus highlighting the role of follower expectations in determining the effectiveness of leadership. It points toward the need for future research to simultaneously test the contingencies and relative importance of paternalistic, authoritarian, transformational, as well as other leadership styles in various cultures as well as to continue exploring the moderating influence of various cultural value orientations on these leadership styles’ follower effects.